Estudio de hábitos de consumo radial de la audiencia juvenil comprendida en edades de 15-19 años en el cantón Salcedo - Chiliquinga Mora, Karla Jesseña (2017)
Local radio offers a large number of radio content aimed at satisfying the information, educational and entertainment needs of various target audiences. The broadcast of radio content is subject to tastes and preferences of the audience. The presence of social networks makes it easy to get information, which leaves aside the public's attention within the traditional coverage. The research, uses the qualitative and quantitative methodology that intends to analyze the habits of radial consumption of the youth audience included in ages of 15-19 years of the canton Salcedo, reflecting, if this audience chooses the radio as their favorite medium forward to other means. Likewise, it is evaluated the schedules of local media, to know if there is content in the local media intended for the youth audience, if it meets the expectations of the listener, enabling, reach the audience with a different style….